Limb flexion-extension counter using IR proximity sensor - Lakshmi Prabha, P; R. Nair, Vishal; Nair, Aishwarya; Debroy, Sayan; Debroy, Sonalika; Amit Patro, K (International Journal of Engineering and Technology, 2018)
People belonging to different age groups whosuffered fractures, temporary limb paralysis, paraplegia and monoplegia and various stages of hypertension (High BP) need to carry out physiotherapy to regain motor control in the limb(s). So this limb flexion extension counter can assist the subject to exercise properly and independently recover with ease. This device will help to monitor parameters such as heart rate, temperature and limb flexion-extension counts. This device can detect the skin temperature while doing exercises using LM35 temperature sensor. The instrument has Arduino UNO as its microcontroller and four sensors mainly an IR heart rate sensor, LM35 temperature sensor, IR proximity sensor for limb flexion-extension counter. A cuff pressure sensor used for measuring the pressure applied to the cuff. The cuff is inflated and fixed the sensors to the upper arm. On flexing the lower arm, the IR proximity sensor generates a light output denoting a count which is displayed in the LCD display. The heart rate sensor and temperature sensor is used for assessing the subject’s vital parameters while exercising. In conclusion doing more exercise causes rise in heart rate and if it goes beyond 90-100 beats per minute exercising should be stopped.